Effect of assistance exercises for the snatch on barbell speed and performance for weightlifters - Khaled Ebada; Ahmed Tamam; Nagy Radwan (Turkish Journal of Kinesiology, 2016)
This study aims to identify Effect of assistance exercises for the snatch on barbell speed and performance for Weightlifters. Applied study on a sample of 14 lifters from the Youth weightlifters team in Beni Suef cities/Egypt of the season 2014/2015, the researcher used experimental method to design two groups; one experimental consisted of 7 lifters and the other control group of 7 lifters. Where the average age of 18.21 ± 0.80 years, height 174.28 ± 6.03 cm, weight 74.14 ± 8.88 kg and age training 3.92 ± 0.91 month. The experimental group underwent an assistance exercises for the snatch program for barbell speed and performance in the snatch, while the control group underwent a training program with exercises classic. Assistance exercises for the snatch program Continued for 8 Weeks 5 times per week and the training session lasted 2 hours. The training program using exercise showed a statistically significant improvement for assistance exercises on barbell speed, velocity (vertical, horizontal) for snatch lift and performance weightlifters. Interest in using assistance exercises for snatch and private exercises of pull, power snatch and squat snatch has an important role in the success of the performance of the snatch. Training according to power curve, speed and time of the barbell trajectory and muscle working performance. The need for evaluation of barbell trajectory during the performance by modern techniques for analysis of kinetic activity links it with training programs for weightlifters. These results must be taken into account by the coaches and weightlifters to use the assistance exercises for snatch to improve the kinetic performance and the level of achievement lifting snatch for weightlifters.